Occupational exposures and sick leave during pregnancy: results from a Danish cohort study - Mette Lausten Hansen; Ane Marie Thulstrup; Mette Juhl; Jette Kolding Kristensen; Cecilia Høst Ramlau-Hansen (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVE: This study aimed to investigate associations between work postures, lifting at work, shift work, work hours, and job strain and the risk of sick leave during pregnancy from 10-29 completed pregnancy weeks in a large cohort of Danish pregnant women. METHODS: Data from 51 874 pregnancies in the Danish National Birth Cohort collected between 1996-2002 were linked to the Danish Register for Evaluation of Marginalization. Exposure information was based on telephone interviews. Hazard ratios (HR) with 95% confidence intervals (95% CI) were calculated by Cox regression analysis, using time of first episode of sick leave as the primary outcome. RESULTS: We found statistically significant associations between all the predictors and risk of sick leave; for non-sitting work postures (HR_range 1.55-2.79), cumulative lifting HR_trend 1.29, 95% CI 1.26-1.31, shift work (HR_evening 1.90, 95% CI 1.73-2.09, HR_night 1.52, 95% CI 1.15-2.01), monthly night shifts HR_trend 1.12, 95% CI 1.11-1.14, increasing weekly work hours HR_trend 0.93, 95% CI 0.91-0.95 and high job strain HR 1.52, 95% CI 1.42-1.63. Some exposures influenced HR in either a positive or negative time-dependent way. CONCLUSION: Our results support previous findings and suggest that initiatives to prevent sick leave during pregnancy could be based on work conditions. Preventive measures may have important implications for pregnant women and workplaces.